Kulturowe źródła obrazu buntownika - Kutyła, Dorota Halina (Civitas. Studia z filozofii polityki, 2013)
The author returns to both Polish and German cultural sources and depictions of rebellion. In Polish culture the basic, even archetypical depiction of warriors comes from Zygmunt Krasiński’s Un-divine comedy [Nie-Boska komedia]. For the German culture it is The Robbers, written by Friedrich Schiller. Both dramas are characterized by the author as cultural models of rebellion and revolution for the two countries. The problems depicted in both books have not only become historical, old and resolved, but they are present in the current times. Due to this fact, the questions of how to change them remain. Since the questions recur it is worth coming back to the culturally depicted solutions.